Sistem Informasi Pendistribusian dan Persediaan Gas Menggunakan Metode Distribution Requirement Planning - Ade Boy Saputra; Fajrillah, Fajrillah; Imam Adlin Sinaga (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2024)
The development of information technology at this time has grown so rapidly that it encourages various agencies or companies to use information technology to obtain useful information to advance their business. But behind the current technological advances, the processing of distribution and inventory data at PT Andalas Jaya Perkasa still uses a logbook or manual. Where if the data is needed at any time, you have to search among piles of data so that it is difficult to search for data because of the large amount of scattered data, and the data storage process that has not been computerized, this causes frequent data loss, besides that PT. Andalas Jaya Perkasa often experiences difficulties in meeting customer demand which results in inefficient inventory management, this can result in excess or shortage of stock, this condition can have an impact on reducing customer service. Based on the above problems, the authors build a gas distribution and inventory information system application using the distribution requirement planning method and supported using supply chain management strategies to improve the quality of service to customers at PT Andalas Jaya Perkasa optimally.